ANALISIS PERANAN KOREAN WAVE TERHADAP DIVERSIFIKASI PRODUK DALAM KONTEKS INOVASI BISNIS BERKELANJUTAN - Putri, Meichya Nirmala; Vanomy, Afrianti Elsye (E-Jurnal Manajemen; Vol 11 No 12 (2022)DO - 10.24843/EJMUNUD.2022.v11.i12.p04, 2022)
This study has the purpose of knowing the role of Korean Wave on product diversification in the context of sustainable business innovation for MSME’s in Batam City. The method used in this research is a qualitative method. Source of data in this study was obtained by conducting interviews with five MSMEs in category of culinary, clothing and beauty commodities who were selected according to predetermined criteria. This study uses content analysis techniques to analyze the whole of interview data followed by triangulation activities with document studies to support the accuracy of the data.. The results of this study indicate that the Korean Wave phenomenon is a unique phenomenon with a very high market share in Batam City along with its role factors in giving birth to business opportunities for MSME actors in Batam City to make efforts to diversify products both horizontally and vertically with the aim of business development innovation and achieving business sustainability from the economic, social and environmental aspects. Keywords: Korean Wave; Product Diversificatio; Innovation; Sustainable Business; MSME.